Charismatic Leadership in Improving the Quality of Islamic Boarding School Education - Humaisi, M. Syafiq; Thoyib, Muhammad (LETIGES, 2025)
The purpose of this study is to understand and analyze the role of charisma in improving the quality of Islamic education processes, curriculum quality, and educational output quality. This study uses a qualitative research approach and modified qualitative analysis. This study was conducted at the Zainul Hasan Genggong Islamic Boarding School, Probolinggo. Data collection was carried out through observation, interviews, and documentation. Analysis was carried out through checking data reduction, data presentation, and concluding. To ensure data credibility, triangulation was used. The results of the study indicate that the role of leaders in improving religious education in Islamic boarding schools through formal and informal education, organizing international guest teacher programs, and providing facilities and infrastructure according to the demands of Salafiyah and modernity. The Islamic boarding school implements a dormitory-based supervision system, integrated mentoring programs such as muhadarah and istighasah, and an effective quality time policy for students in terms of supervision. The Islamic boarding school leaders advocate for improving alumni competency through entrepreneurship training, community service, and the formation of alumni networks and international cooperation between Islamic boarding schools related to graduate quality. In addition, strengthening the university's external environment includes developing alumni networks at home and abroad, university relations with the community, and providing services and support to the community.